2006
DOI: 10.1111/j.1365-2486.2006.01131.x
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the uncertainty in annual net ecosystem carbon exchange: spatial variation in turbulent fluxes and sampling errors in eddy‐covariance measurements

Abstract: Above forest canopies, eddy covariance (EC) measurements of mass (CO 2 , H 2 O vapor) and energy exchange, assumed to represent ecosystem fluxes, are commonly made at one point in the roughness sublayer (RSL). A spatial variability experiment, in which EC measurements were made from six towers within the RSL in a uniform pine plantation, quantified large and dynamic spatial variation in fluxes. The spatial coefficient of variation (CV) of the scalar fluxes decreased with increasing integration time, stabilizin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
121
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 149 publications
(127 citation statements)
references
References 50 publications
5
121
1
Order By: Relevance
“…When applying a two-tower based approach it is important to assure that systematic differences of the measured fluxes, which are partly caused by within-site or among-site heterogeneity, are not attributed to the random error estimate of the measured NEE. Our assumption that even within a site with apparently one uniformly distributed vegetation type (and for very short EC tower distances) land surface heterogeneity can cause significant spatial and temporal variability in measured NEE is, e.g., supported by Oren et al (2006). They found that the spatial variability of ecosystem activity (plants and decomposers) and leaf area index within a uniform pine plantation contributes to about half of the uncertainty in annual eddy covariance NEE measurements while the other half is attributed to micrometeorological and statistical sampling errors.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…When applying a two-tower based approach it is important to assure that systematic differences of the measured fluxes, which are partly caused by within-site or among-site heterogeneity, are not attributed to the random error estimate of the measured NEE. Our assumption that even within a site with apparently one uniformly distributed vegetation type (and for very short EC tower distances) land surface heterogeneity can cause significant spatial and temporal variability in measured NEE is, e.g., supported by Oren et al (2006). They found that the spatial variability of ecosystem activity (plants and decomposers) and leaf area index within a uniform pine plantation contributes to about half of the uncertainty in annual eddy covariance NEE measurements while the other half is attributed to micrometeorological and statistical sampling errors.…”
Section: Introductionmentioning
confidence: 89%
“…It is expected that systematic differences in measured NEE caused by spatially variable land surface properties are stronger during the night than during the day since they affect respiration more directly than photosynthesis (see, e.g., Oren et al, 2006). Moreover, during night-time and/or winter (positive NEE), some conditions associated with lower EC data quality such as low turbulence, strong stability, and liquid water in the gas analyzer path prevail more often than in summer and/or daytime (negative NEE).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The stem density is derived based on the assumption that the crowns are randomly distributed in space, and the LAI is derived based on the assumption that the foliage volume density is 0.7 m 2 /m 3 . ments, (2) random variation from flux tower measurements due to the dynamic nature of the flux footprint [Oren et al, 2006], and (3) errors in model parameters in PenmanMonteith equation. If we consider the daytime trend for the entire growing season, LE from GCR better matches with the measured LE than that from UCR ( Figure 7).…”
Section: Latent Heat Exchangementioning
confidence: 99%
“…If we consider the daytime trend for the entire growing season, LE from GCR better matches with the measured LE than that from UCR ( Figure 7). When comparing the ensemble mean diurnal trends, we essentially removed the high frequency random errors from the eddy flux measurements, which could account for 50% of the variation at the half hourly time step [Oren et al, 2006].…”
Section: Latent Heat Exchangementioning
confidence: 99%